ANALISIS PEMILIHAN ALAT KONTRASEPSI MODERN DI KECAMATAN KEMAYORAN - Zulaika; Dewi Susilawati (INFOKES (Informasi Kesehatan), 2022)
In launching the Family Planning Program which aims to maintain a distance between pregnancies and it is enough to have only two children, so that the program can be achieved, one of them is by using modern contraceptives. Modern contraceptives are divided into two, namely hormonal and non-hormonal contraceptives. Participating in the family planning program is expected to improve maternal health and increase non-hormonal family planning users. This study aims to analyze the selection of modern contraceptives in Kemayoran sub-district. The research process is cross-sectional, conducted on 110 Kb acceptor mothers in Kemayoran District. The results showed that the knowledge variable had P=0.055 and OR=2.674, attitude variable P=0.0001 and OR=16,875, information exposure variable P=0.036 and OR=1.096, husband's role variable P=0.0001 and OR=6.333 . Counseling about family planning and the selection of modern contraceptives should be carried out continuously and health workers always advise acceptors on non-hormonal contraception. In addition, prospective acceptors are advised to always follow the counseling organized by the Central Jakarta Administration City PPAPP Sub-Department and receive information related to the selection of contraceptives from both mass media and electronic media. A good husband's role and support is also needed so that the acceptor can change his attitude in choosing contraceptives not based on comfort but because it is in accordance with their needs and health. Keywords: Modern contraceptives, Non-hormonal acceptors, Family Planning Program